A Modfied Nuss Procedure for Recurrent Pectus Excavatum of Adults - Wang, Lei; Bi, Rui; Xie, Xiao; Xiao, Haibo; Hu, Fengqing; Jiang, Lianyong (Frontiers in Surgery, 2022)
Background Limited data exist for adults with recurrent pectus excavatum (PE) treated with minimally invasive surgical repair. Methods Between July 2008 and December 2020, forty-two adult patients with recurrent PE underwent a modified Nuss procedure with a newly designed bar in our centre. A small vertical subxiphoid incision was used to separate severe adhesions when necessary. Multiple steel wires were sutured, and the rib space was narrowed to firmly fix the bar. The primary end point was Haller index change after operation. The secondary end points included length of stay after operation, short-term and long-term complications. Results The mean patient age was 22.02±3.49 years. The mean Haller index was 4.59±1.09. A subxiphoid incision was performed in 12 patients. Thirty-nine patients had one bar placed, and 3 patients required two bars. Sixteen patients had 3 or more wires fixation, and 4 patients needed to have their intercostal space narrowed. There was no perioperative death, and the mean hospitalization was 5.57±2.47 days. The Haller index reduced to 3.03±0.41 after the operation (t=11.85, p＜0.001). During the follow-up, there were 3 patients who developed noninfective wound effusion; bar rotations occurred in 3 patients. Twenty patients had the bar removed, post-bar removal Haller index was significantly reduced compared to the preoperative Haller index (2.89±0.37 vs. 4.72±1.05，t=8.96, p＜0.001). Conclusions The modified Nuss procedure with a new titanium alloy bar can achieve good results for adult patients with recurrent PE.